Effect of acetaminophen on the progression of renal damage in adenine induced renal failure model rats - Kadowaki, D.; Sumikawa, S.; Arimizu, K.; Taguchi, K.; Kitamura, K.; Ishitsuka, Y.; Narita, Y.; Irie, T.; Chuang, Victor; Maruyama, T.; Otagiri, M.; Hirata, S. (Elsevier, 2012)
Aims: Acetaminophen is a safe antipyretic and analgesic drug within the clinically recommended dosage range, but overdose can cause fatal liver and or kidney damage. Most of the nonsteroidal anti-inflammatory drugs (NSAIDs) exert their analgesic effect via inhibition of cyclooxygenase, which also results in a reduction of renal blood flow. Therefore, the use of NSAIDs in pain treatment for chronic kidney disease (CKD) patients is of particular concern. Acetaminophen lacks the anti-inflammatory and anti-coagulatory properties of the NSAIDs. In this study, we investigate whether acetaminophen has an impact on the progression of renal failure. Main methods: Acetaminophen (150 mg/kg/day or 750 mg/kg/day) or indomethacin (5 mg/kg/day) was orally administered to adenine-induced chronic renal failure model rats for 4 weeks. The plasma concentrations of acetaminophen and its metabolites were measured during the treatment period; renal function and oxidative stress in the rats were also monitored. Key findings: Indomethacin significantly decreased the survival rate of renal failure model rats. In contrast, both low (150 mg/kg) and high (750 mg/kg) doses of acetaminophen improved the survival rate. The progression of renal failure was attenuated by acetaminophen (750 mg/kg) after administration for 2 weeks. The metabolites of acetaminophen were found to accumulate in plasma. Plasma glutathione concentration had significantly recovered after acetaminophen administration. Significance: Acetaminophen has no effect on the progression of renal damage in adenine-induced renal failure model rats. This result is in part due to acetaminophen's antioxidant activity. These results suggest that acetaminophen is a suitable analgesic agent for treating CKD patients.